Relationship between energy deficits and body composition in elite female gymnasts and runners - Deutz, R. C.; Benardot, D.; Martin, D. E.; Cody, M. M. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The purpose of this study was to evaluate energy balance and body composition in 42 gymnasts (x[overbar] age = 15.5 yr) and 20 runners (x[overbar] age = 26.6 yr), all of whom were on national teams or were nationally ranked. Methods: Athletes were assessed for body composition using DEXA and skinfolds, and energy balance was determined with a Computerized Time-Line Energy Analysis (CTLEA) procedure. Results: Results from the CTLEA were assessed as the number of within-day energy deficits (largest and frequency) and within-day energy surpluses (largest and frequency). There was a significant difference (P = 0.000) in the x[overbar] number of hourly energy deficits > 300 kcal experienced by gymnasts (9.45 ± 6.00) and runners (3.70 ± 5.34). There was also a significant difference (P = 0.001) in the x[overbar] number of hourly energy surpluses > 300 kcal experienced by gymnasts (1.40 ± 3.04) and runners (6.20 ± 5.50). The x[overbar] largest daily energy deficit was 743 (± 392) kcal for gymnasts and 435 (± 340) kcal for runners. The x[overbar] largest daily energy surplus was 239 (± 219) kcal for gymnasts, and 536 (± 340) kcal for runners. There was a significant relationship between the number of daily energy deficits > 300 kcal and DEXA-derived body fat percent for gymnasts (r = 0.508; P = 0.001) and for runners (r = 0.461; P = 0.041). There was also a negative relationship between the largest daily energy surplus and DEXA-derived body fat percentage for gymnasts (r = -0.418; P = 0.003). Using the energy balance variables, age, and athlete type (artistic gymnast, rhythmic gymnast, middle-distance runner, long-distance runner) as independent variables in a forward stepwise regression analysis, a small but significant amount of variance was explained in DEXA-derived (P = 0.000; R2 = 0.309) and skinfold-derived (P = 0.000; R2 = 0.298) body fat percent by the number of energy deficits > 300 kcal and age. Conclusions: These data suggest that within-day energy deficits (measured by frequency and/or magnitude of deficit) are associated with higher body fat percentage in both anaerobic and aerobic elite athletes, possibly from an adaptive reduction in the REE. These data should discourage athletes from following restrained or delayed eating patterns to achieve a desired body composition.